Organizing Foreign Language Lessons in Primary Education (Eurasian Journal of Humanities and Social Sciences, 2023)
In this article, the task and skills of pedagogues to improve foreign language skills in elementary school students, how important foreign language is for students, the correct organization of foreign language classes, different types of foreign language classes the use of methods is discussed.